A model for incorporating “indigenous” postnatal care practices into the midwifery healthcare system in Mopani district, Limpopo Province, South Africa - Mulaudzi, Fhumulani Mavis (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.